Postoperative Pain Comparison: Manual K-Files vs Pedoflex Rotary Files in Primary Molar Root Canals (Academia Journal of Medicine, 2024)
This study evaluated postoperative pain in pediatric  patients after root canal treatment with two file systems:  Manual K-files and Pedoflex Rotary files. Sixty children,  aged 6-10, were randomized into two groups of 30. Pain  was assessed using a Visual Analog Scale (VAS) at 6, 12,  24, and 48 hours post-treatment. Results showed  significantly lower pain levels in the Pedoflex Rotary file  group at all time points (mean VAS at 6 hours: 2.4 vs. 3.8;  at 12 hours: 1.8 vs. 3.2; at 24 hours: 1.2 vs. 2.5; at 48 hours:  0.6 vs. 1.8). Pedoflex Rotary files provide a more  comfortable postoperative experience.
Keywords: Pulpectomy; Deciduous tooth; Rotary files